Theoretical analysis of the informal economy in Latin América: a systematic review - Surpachin Miranda, Iván Enrique; Montoya Vargas, Regulo; Lino Gamarra, Augusto Homero; Medina Sotelo, Cristian Gumercindo; Cueva-Quezada, Nilton Isaias (Cuadernos de Administración, 2024)
The informal economy, or informality, remains a pervasive issue in developing countries, including those in Latin America. This study delves into the key theoretical aspects of informality, examining its characteristics, impacts, and particularly its contribution to economic growth. Utilizing a systematic review methodology and the PRISMA method, the study selected twenty-two pertinent articles from databases such as Web of Science, Scopus, and SciELO. The findings reveal that the informal economy significantly impacts economic growth, adversely affecting productivity, formal employment creation, and tax collection. The conclusions underscore that informality detrimentally affects regional economic development due to regulatory deficiencies, low productivity, tax evasion, and inadequate labor protection. Addressing these challenges necessitates the implementation of policies and strategies focused on enhancing the education and training of informal workers, reducing administrative and fiscal barriers, improving infrastructure and basic services, reinforcing regulatory enforcement, and promoting the formalization of informal enterprises.